Pemberdayaan Usaha Kerajinan Anyaman Industri Kreatif Penghasil Bambu Desa Kaliwungu Semarang - Annisa Fajri; Hajar Hajar; Olivia Aldira; Rini Adiningtyas; Ratna Shofiyatul Fitriyah; Rana Rosyana; Aulia Nur Pratiwi; Rahma Isyami Salsabila; Raihan Rachman Tsabata; Ainurrohmah Ainurrohmah; M Mifbakhul Maulana (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2023)
The creative economy aims to develop small creative industries in the hope that an economic product produced can open up new markets and jobs. The development of a creative industry in one of the villages that has natural resource potential in the form of a bamboo forest which is still underutilized. The solution to the problem that we offer is to distribute woven bamboo products to cities or out of town, helping people produce goods made from woven bamboo that are more innovative, attractive, and modern so that woven bamboo products are not outdated and are no less interesting than other products made of metal, glass, so on. In addition to helping the village community regarding the sale of their woven products so that it is easier for the community to sell products other than to the only middlemen in the village, helping the community to earn income and providing satisfaction for the consumer.